Demystifying the Monoclonal Gammopathies of Renal Significance. Issue 3 (November 2017) - Hogan, Jonathan J.
The monoclonal gammopathies of renal significance (MGRS) are paraprotein-mediated diseases of the kidney in patients who do not meet criteria for multiple myeloma or systemic lymphoma. The diagnosis requires a kidney biopsy, and management is geared toward detection and treatment of the underlying plasma or B cell clone that is producing the pathogenic paraprotein. This approach is extrapolated from well-studied paraprotein-mediated diseases such as multiple myeloma and AL amyloidosis. In this review, we aim to demystify the workup and treatment of the MGRS disorders.